Intercropping of banana and pineapple in rubber plantations in Tripura - Roy S; Choudhury M; Dey S K; Nazeer M A; Raj S (Indian Journal of Natural Rubber Research, 2001)
The effect of two cropping systems involving two intercrops, banana and pineapple, on soil chemical properties, growth of rubber, biomass production, nutrient recycling, productivity and returns was investigated during the first four years (1996-97 to 1999-2000) growth period of rubber in North-Eastern India, Agarthala, Tripura. In the first system (Model I), intercrop strip consisting of five rows of pineapple and two rows of banana was planted in between four strips of rubber with a stand of 550 rubber plants per ha and in the second system (Model II), one of banana and two rows of pineapple were planted in alternate gaps with 470 rubber plants per ha. Continued fertilizer use under these two systems showed increase in available phosphorus and calcium. The growth of rubber was better and biomass production as well as nutrient recycling was higher in MOdel I. High yield and benefit:cost ratio of banana and pineapple established the economic feasibility of growing these intercrops. The maximization of yield and returns from the intercrops was possible by increasing the plant density (as in Model I) without adversely affecting the soil properties.
Keywords: Banana; Benefit-cost ratio; Hevea brasiliensis; India; Intercropping; Non-traditional regions; Pineapple; Tripura